Molecular Scale Modeling of Membrane Water Treatment Processes - Ridgway, H.; Gale, Julian; Hughes, Zak; Stewart, M.; Orbell, J.; Gray, S. (Wiley-VCH Verlag GmbH & Co. KGaA, 2013)
Membrane processes have become commonplace in the water industry since the 1990s, with low-pressure microfiltration (MF) and ultrafiltration (UF) membranes used for the removal of particles and bacteria, whereas high-pressure membranes, such as reverse osmosis (RO) and nanofiltration (NF) membranes, are used for desalination and removal of color and trace organics of interest. Water transport and salt/color rejection in RO membranes occurs at the molecular scale, and molecular models have been used to develop an understanding of these processes. For MF/UF membranes, organic fouling is an operational problem that lends itself to modelling at the molecular scale, but there has been little emphasis on this approach to date. This chapter examines three distinct areas relevant to the molecular modeling of membrane-based water treatment processes. First, Section 10.2 critically discusses the progress and methods used to study, at the molecular level, the structure and properties of high-pressure polymeric membranes, as well as the deficiencies currently present in this approach. Second, Section 10.3 analyzes the current state of research on zeolites as the most promising candidate for inorganic membrane material and describes the application of molecular modeling in studying the transport of water and ions through zeolite materials, as well as providing further insights into ion selectivity. Finally, Section 10.4 investigates the potential of molecular modelling to be applied to the problem of organic fouling of polymeric membranes. Such an approach could provide insights into the new methods to ameliorate organic fouling.